Характеристика ростових процесiв вирезуба Rutilus frisii (Nordmann) в умовах Днiстровського водосховища - Худий, О. I.; Худа, Л.В.; Цапок, О.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
The growth characteristics of fishes enables to estimate a level of the well-being for separate individuals and populations. However, such researches demand the availability of a significant volume of animal materials. It can become a certain difficulty when the community of infrequent species is studied, as small samplings do not allow one to execute high-quality population researches. Applications of various extrapolation and approximation methods can become an output from such a situation. The application of such an approach to studying the nonpassage populations of a infrequent species, Rutilus frisii (Nordmann), is considered.